Curriculum Reform in Indonesia: A Literature Review on Educational Policy Dynamics, Vocational Relevance, and Digital Inequality - Darwis, Muh.; Jamaluddin, Jamaluddin; Nasir, Nasir (Program Pascasarjana Universitas Negeri Makassar, 2025)
Educational policy plays a fundamental role in shaping the direction and effectiveness of curriculum reform, particularly in rapidly transforming nations such as Indonesia. This literature review explores the evolution of educational policy in Indonesia and its implications for curriculum development, focusing on decentralization, stakeholder involvement, and the integration of digital technology. Drawing upon studies from 2020 to 2025, this review identifies key challenges such as inequality of access, fragmented policy implementation, and insufficient training for educators. It also highlights the influence of globalization, neoliberal ideologies, and socio-cultural diversity. The study emphasizes the need for inclusive, adaptive, and context-sensitive policies that account for regional disparities and the importance of vocational education and technological innovation in preparing future-ready learners. Recommendations include strengthening stakeholder engagement, adopting localized curriculum approaches, investing in teacher capacity-building, and ensuring policy coherence across governance levels. This comprehensive synthesis offers insights for policymakers, educators, and researchers working toward equitable and transformative educational reform.